Effects of thyroid status on renal calcium and magnesium handling. - McCaffrey, C (1984)
Renal calcium and magnesium handling was studied in rats with chronic thyroid hormone deficiency or excess, hyperthyroidism. Mean kidney weight of the thyroid deficient rats was 42% of age matched, euthyroid and hyperthyroid animals and glomerular filtration rate was 71% of normal. Fractional sodium excretion was consistently elevated in thyroid deficient rats (0.26%) as compared to euthyroid (0.07%) and hyperthyroid animals (0.07%). Urinary calcium excretion (0.39%) was also elevated and parallel to sodium excretion in thyroid deficiency. Despite this renal leak of sodium and calcium, thyroid deficient animals conserved magnesium much more efficiently than either euthyroid or hyperthyroid rats (5.7% vs 17.4% respectively). Plasma magnesium concentration was elevated by acute MgCl2 infusions to determine the reabsorptive capacity of magnesium. Thyroid deficient rats reabsorbed 15-30% more of the filtered magnesium at any given plasma concentration. Although these effects on electrolyte reabsorption are modest compared to the hemodynamic alterations, the data suggest that thyroid hormone has a direct effect on the tubule which if chronically absent results in subtle sodium and calcium wasting and renal retention of magnesium. Administration of thyroid hormone to euthyroid or thyroid deficient rats twenty-four hours prior to experimentation had no effect on calcium and magnesium handling.